Analysis of Students' Conceptual Difficulties in Learning Linear Aljabar in Higher Education - Siti Zubaidah Dalimunthe (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze students’ conceptual difficulties in learning Linear Algebra at STAI Al Hikmah Tebing Tinggi. The research employed a descriptive qualitative approach, with data collected through diagnostic tests, in-depth interviews, and documentation. The results indicate that students experience significant conceptual difficulties in four main aspects: systems of linear equations, matrix operations and their properties, elementary row operations, and abstract concepts such as vector spaces and linear transformations. The factors contributing to these difficulties include weak prerequisite knowledge, ineffective teaching methods, a lack of meaningful practice problems, limited learning resources and instructional media, and low learning motivation. These conceptual difficulties hinder students’ understanding of subsequent courses that require Linear Algebra as a prerequisite. Therefore, improvements in instructional strategies oriented toward conceptual understanding, the use of visualization technologies, the development of contextual learning materials, and the implementation of active and collaborative learning approaches are necessary to enhance the quality of Linear Algebra instruction.